The Strengthening of Tax Court Independence in the Indonesian Judicial System - Virna Regika; Muspita Sari; Mirwan Fikri Muhkam; Irfan Amir (Faculty of Law, University of Merdeka Malang, 2024)
This study aims to analyze the strengthening of the Tax Court's independence within Indonesia's judicial system following the Constitutional Court Decision No. 26/PUU-XXI/2023. The ruling alters the administrative structure of the Tax Court from a dual system to a unified system under the Supreme Court, transferring oversight authority that was previously under the Ministry of Finance. This research employs a normative juridical method with a statutory, conceptual, and case-based approach. The findings indicate that the implementation of this unified system is a significant step toward enhancing the independence and impartiality of the Tax Court, which was previously vulnerable to executive interference. Furthermore, this change aligns with the principle of the separation of powers as advocated by Montesquieu, emphasizing the necessity of separating judicial power from executive and legislative branches. The Constitutional Court Decision No. 26/PUU-XXI/2023 is expected to strengthen the role of the Tax Court as an independent judicial body, free from government influence, and tasked with upholding justice for taxpayers in Indonesia. This study provides a crucial contribution to understanding the constitutional implications of this decision for the judicial system in Indonesia. How to cite item: Regika, V., Sari, M., Muhkam, M., & Amir, I. “The Strengthening of Tax Court Independence in the Indonesian Judicial System.” Jurnal Cakrawala Hukum, 15(1). (2024):80-90. DOI: https://doi.org/10.26905/idjch.v15i1.14276.